2020
DOI: 10.3390/f11040412
|View full text |Cite
|
Sign up to set email alerts
|

Initial Responses in Growth, Production, and Regeneration following Selection Cuttings in Hardwood-Dominated Temperate Rainforests in Chile

Abstract: Hardwood-dominated forests in south-central Chile have shade-tolerant and mid-tolerant tree species capable of regenerating and growing well in partial shade. To test the potential for using an uneven-aged silviculture in these forests, we established single-tree selection treatments at two mid-elevation sites within the Evergreen forest type in the Coastal range (Llancahue and Los Riscos, 40-42 • S Lat). They had an average initial basal area of 70-80 m 2 ha −1 . In each stand, we established four 2000 m 2 pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…We chose to assess changes through the OGI and found that it increased in the secondary and mature forests subjected to variable-density thinning and irregular shelterwood, respectively, but declined in the older forest subjected to single-tree selection cutting. While this might be expected, especially since the selection cut defined a maximum residual diameter (Donoso et al, 2020b), these results illustrate that restoring old-growth attributes through ecological silviculture should aim to attain a percentage of the OGI (e.g., ≈70%; Ponce et al, 2019). It also might reconsider the variables included to calculate this index, such as coarse woody debris (see also Acker et al, 1998).…”
Section: Discussion and Perspectivesmentioning
confidence: 86%
See 1 more Smart Citation
“…We chose to assess changes through the OGI and found that it increased in the secondary and mature forests subjected to variable-density thinning and irregular shelterwood, respectively, but declined in the older forest subjected to single-tree selection cutting. While this might be expected, especially since the selection cut defined a maximum residual diameter (Donoso et al, 2020b), these results illustrate that restoring old-growth attributes through ecological silviculture should aim to attain a percentage of the OGI (e.g., ≈70%; Ponce et al, 2019). It also might reconsider the variables included to calculate this index, such as coarse woody debris (see also Acker et al, 1998).…”
Section: Discussion and Perspectivesmentioning
confidence: 86%
“…In a mature N. dombeyi-dominated forest, we evaluated an irregular shelterwood cutting (sensu Raymond and Bédard, 2017). In a partially harvested old-growth forest, we evaluated a single-tree selection cut (Donoso et al, 2020b). Harvests in these forests provided mostly firewood that allowed profitable operations (personal observation Donoso et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…We recorded species, dbh, tree form and health (each in three categories), and the crown position (dominant, codominant, intermediate, suppressed/ submerged) following the forest inventory protocols of Prodan et al (1997). In addition, we measured the top height of a stratified subsample by tree diameter classes (Table 2) per plot with a VERTEX IV ultrasonic hypsometer (Haglof Inc., Madison, Mississippi, USA) to fit height-diameter functions, and estimate heights and volumes of all trees (according to the functions given in Drake et al (2003) for Hueicolla and in Donoso et al (2020a) for Llancahue). We measured 88 trees in Hueicolla and 134 trees in Llancahue from the new cohort (residual trees from the shelterwood cuttings were not included).…”
Section: Data Collectionmentioning
confidence: 99%
“…With the dbh of each tree per plot, we calculated the basal area (G) and estimated the height (h) and volume (V) of each tree according to species (Drake et al 2003;Donoso et al 2020a). With this information, we determined stand level (per ha) values for tree density (N, number of trees), basal area, and volume after treatment (Hueicolla: 1982, Llancahue: 2009 and for the last measurement (2021 to 2022).…”
Section: Estimation Of Stand Variablesmentioning
confidence: 99%
“…We planned for a maximum residual diameter of 80 cm but needed to leave 20-25% of the residual basal area in larger trees due to their great abundance in these old-growth forests. Plots were re-measured 5-6 years after the cuttings (Donoso et al 2020a). At Llancahue, the PAI in diameter of individual trees was significantly greater in the treatment with lower residual densities, especially for mid-tolerant species in lower diameter classes (5-20 cm).…”
Section: Uneven-aged Silviculture In Partially Cut Old-growth Forestsmentioning
confidence: 99%